IMPLEMENTATION OF GENETIC ALGORITHM FOR STUDENT PLACEMENT PROCESS OF COMMUNITY DEVELOPMENT PROGRAM IN UNIVERSITAS GADJAH MADA - Nanang Arfandi; Faizah . (Jurnal Ilmu Komputer dan Informasi, 2013)
Community Development Program (CDP) is a required subject in Universitas Gadjah Mada for undergraduate students to earn a bachelor’s degree. One of the big problem in CDP implementation is student placement process into available thematic units. Each unit as much as possible filled by students which have balanced composition based on specified criteria. Balances in gender ratio and clusters composition are needed to have an objective assigned team students in a unit. In this paper, a genetic algorithm is proposed to solve this placement problem. The results of this paper is a simulation in CDP student placement process which using genetic algorithm to produce recommendation units which have good composition.